(untitled) (Bangladesh Journal of Medical Microbiology, 2016)
Antimicrobial resistance has been coming up as one of the challenging business for treating domiciliary and nosocomial infections. The present study compared rate of resistance towards different commonly used antibiotics for common bacterial pathogens isolated during 2001 to 2003. Regarding Escherichia coli, mentionable increase (p<0.01) of resistance was noted against ceftazidime (47% to 77%) and ceftriaxone (43% to 71%). Imipenem (2% to 1%) and pefloxacin (40% to 17%) showed decreased trend. For Staphylococcus aureus, marked increase in resistance was shown against almost all antibiotics except co-trimoxazole (55% to 57%). Mentionable increase in resistance (p<0.05 and p<0.001, respectively) was noted against ciprofloxacin (17% to 43%) and ceftriaxone (28% to 83%). Although, oxacillin resistance increased from 22% to 42% but no resistance against vancomycin was noted during this period. Strains of Pseudomonas species showed increase (p<0.05) in resistance against ciprofloxacin (47% to 71%), ceftriaxone (50% to 74%) and ceftazidime (39% to 58%). Carbenicillin showed decreased resistance (92% to 50%) and none of the strains was found resistant to imipenem. Emphasis was given towards judicial use of antibiotics by followig local antibiogram. Bangladesh J Med Microbiol 2007; 01 (01): 04-09